Avaliação da eficiência de vacinas antitetânicas de uso veterinário - Eduardo Henrique Moreira Lima (2006)
Tetanus is an infectious neurological syndrome caused by the action of the tetanus toxin, produced by Clostridium tetani, which acts in the central nervous system, characterizing itself for a spastic paralysis. The antibody response to the C. tetani component of eight commercial vaccines was evaluated by the mice serum neutralization test with rabbit and guinea pigs sera. The codified vaccines T2, T4, T5 and T8 induced titles of C. tetani antitoxin superior to the recommended minimum title of 2,5 IU/ml. The vaccines T1, T3, T6 and T7 did not induce protection titles. The 50% of the C. tetani vaccines commercialized in Brazil were unable to induce the minimum antibody response recommended for the approval of the product